Flora of Bahia - Droseraceae Salisb. - Silva, Tânia Regina da (SITIENTIBUS série Ciências Biológicas, 2007)
The present study is part of the project “Flora of Bahia”. Droseraceae is represented in Bahia state by the genus Drosera, with five species: Drosera chrysolepis Taub. D. communis A.St.-Hil., D. intermedia Dreves & Hayne, D. montana A.St.-Hil., D. sessilifolia A.St.-Hil. Description and illustrations, as well as comments on geographic distribution, phenology and the variability of the species are presented.